Implementation of Discussion Teaching Method to Improve PAI Learning Outcomes of SMK Al Karimah Bodak Students - Eni Wahyuni; Zainudin Zainudin (Edumaspul: Jurnal Pendidikan, 2024)
A common problem with Madrasah learning systems is the inadequate quality of their educational programmes, which prompted this study. The purpose of this research is to shed light on how SMK Al Karimah Bodak used discussion approaches to enhance PAI learning outcomes in an effort to improve students' poor performance in the subject. Qualitative methods are used, with data collected via observation and questionnaires. Previous studies have shown that lecturing with question and answer sections is the most effective way for instructors to use PAI in the classroom. The small group discussion approach is used in this learning process. Affective students may absorb information effectively, and psychomotor students can be psychologically actively engaged in lecture-based learning outcomes, in terms of cognitive growth. At the third meeting, students' cognitive learning results in discussion-based classrooms started to decline. Students are able to take an active role in psychomotor learning and to receive information effectively in the emotional learning domain.